Metabolic rate shapes differences in foraging efficiency among honeybee foragers. (28th September 2022) - Cassano, Julian; Naug, Dhruba
Abstract: Metabolic rate is the rate at which organisms process energy and is often considered as the fundamental driver of life history processes. The link between metabolic rate and life history is critically mediated via foraging, which shapes the energy acquisition patterns of an individual. This predicts that individuals with different metabolic rates likely vary in their foraging strategies, although such a link has rarely been empirically investigated in the context of optimal foraging theory—a powerful framework for understanding how animals maximize their foraging returns. Many central place foragers such as honeybees maximize their energetic efficiency rather than the rate of energetic gain, given the critical role of energetic costs in foraging decisions. We therefore tested if individuals with low and high metabolic rates differ in efficiency maximization, using genetic lines of honeybees with different metabolic rates. Our results show that low metabolic rate foragers visit more flowers during a foraging trip and have a higher energetic efficiency than high metabolic rate foragers in both low and high resource conditions. We discuss the significance of these results in the context of division of labor and the adaptive role of phenotypic diversity in metabolic rate in a social insect colony. Lay Summary: Metabolic rate is often cited as a primary driver of life history because it determines the energy that is available for behavior. We tested the foraging performance of honeybees that had been genetically selected for either low or high metabolic rate, and found that low-metabolic-rate bees visited more flowers in a foraging trip than high-metabolic rate bees, and also displayed higher energetic efficiency under both low- and high-resource conditions.